Project management for digital projects with collaborators beyond the library. Issue 2 (2nd October 2017) - Burress, Theresa; Rowell, Chelcie Juliet
ABSTRACT: Librarians are increasingly embracing project management to guide their work outside of routine library operations. Some humanities scholars, too, especially within the digital humanities community, are bringing project management techniques to bear on scholarly digital projects. We argue that librarians and their diverse collaborators can apply project management practices to a broad range of research, teaching, and learning projects with collaborators beyond the library. Two case studies illustrate this argument, one from each author's experience: creating a community biodiversity wiki for West-Central Florida and redesigning an interdisciplinary first-year seminar around creating 3-D models of historic Venetian buildings.